A description of practices of analgesia administration by advanced life support paramedics in the City of Cape Town - Matthews, Ryan (Division of Emergency Medicine, 2016)
Introduction: Emergency Medical Services (EMS) are ideally placed to provide relief of acute pain and discomfort. EMS frequently follow locally prescribed guidelines and have a variety of qualifications each with differing capabilities and scopes of practice. The objectives of this study are to describe prehospital pain management practices by EMS in the Western Cape, South Africa. Methods: A retrospective descriptive survey was undertaken of analgesic drug administration by advanced life support (ALS) paramedics. Patient care records (PCRs) generated in t he City of Cape Town during an 11 month period containing administrations of Morphine, Ketamine, Nitrates and 50% Nitrous Oxide/Oxygen were randomly sampled. Variables studied were drug dose, dose frequency, and route of administration, patient age, gender, disorder and call type as well as qualification and experience level of the provider. Results: A total of 530 PCRs were included (N=530). Morphine was administered in 70% (95% CI 66 - 74, n=371) of cases, Nitrates in 37 %(95% CI 33 - 41, n=197) and Ketamine in 1.7% (95% CI 1 - 3, n=9) of cases. A total of 5mg or less of Morphine was administered in 75% (95% CI 70 - 79, n=278), with the mean dose being 4mg (IQR 3 - 6). Single doses were administered in 72.2% (95% CI, 67 - 77, n=268) of Morphine administrations, 56% (95% CI, 21 - 86, n=5) of Ketamine administrations and 82% (95% CI, 76 - 87, n=161) of Nitrate administrations. Chest pain was the reason for pain management in 43% (n=226) of cases. ALS providers have a median experience level of 2 years (IQR2 - 4). Conclusion: ALS providers in the Western Cape appear to use low doses of Morphine, with most analgesia administered as a single dose. Chest pain is an important reason for drug administration in acute prehospital pain. Paramedics do not appear to be using a weight based nor a titration based strategy.